Masterclasse: Le répertoire français pour piano seul ou accompagné du début du XIXe siècle - Montebugnoli, Luca (Paris; Versailles La Nouvelle Athènes - Centre du piano romantique and Centre de Musique Baroque de Versailles (CMBV), 2024)
Organized by La Nouvelle Athènes – Centre du piano romantique and the Centre de Musique Baroque de Versailles, this masterclass focused on early 19th-century French repertoire for piano, both solo and with accompaniment. Held on two historic square pianos by Erard Frères (1806 and 1815), it brought together 15 selected participants—pianists, cellists, and flutists—at the Bachelor and Master levels. The sessions were introduced by a presentation on the early history of French pianism and the development of French pianos.
FRIS
0
Keywords: Declassifying the Classics: Rhetoric, Technology, and Performance, 1750-1850